Design of integrated rectangular SIW filter microstrip patch antenna for wireless communications - Sam, Weng Yik (2014)
This thesis presents the design and development of an integrated substrate integrated waveguide (SIW) filter and microstrip patch antenna, which utilizes cascaded and multilayered techniques. Integrated method contributes to the reduction of the overall design size in front-end subsystems as well as in manufacturing cost. The first design process was developed using the basic concept of filter with the characteristics of the circuit transformation of lowpass prototype network for filter, antenna and integrated filter and antenna with the sequence procedure as a starting point. The next process involved the designing of Chebyshev bandpass for filter, antenna and integrated filter and antenna at desired frequency based on single- and dual-mode. The second and third design process were developed using planar structure based on SIW technology and patch antenna. The concept of SIW was formulated from a standard conventional rectangular waveguide by a set of design rules. Meanwhile, microstrip patch antenna was designed based on the procedures and techniques in order to integrate with SIW filter. Integrated method using cascaded and multilayer are developed from the combination between SIW filter and patch antenna. Two commercial software programs that were used in the design and development of integrated SIW filter and antenna bandpass filter namely Advanced Design System (ADS) software, and CST Studio Suite software. All designs were simulated, manufactured and measured. The experimental results showed good agreement with the simulated results. The main benefits of the integrated SIW filter and microstrip patch antenna are the reduction of the overall size, ease to fabricate, low in cost and the use of standard printed circuit board process. This new novel of microwave filters is considered suitable and is an alternative solution for 3G, ISM, WLAN and LTE applications without an addition of external common impedance network on the systems.